Pengaruh Regional Spillover Terhadap PDRB Daerah istimewa Yogyakarta Tahun 1996-2010 - Dityawarman El Aiyubbi; Diana Wijayanti (Jurnal Aplikasi Bisnis, 2016)
This study intends to determine effect of spillover regional to PDRB in Yogyakarta form the year 1996 to .2010. Yogyakarta has a very distinctive characteristics compared to other regions with the relatively low economic growth. As many as 15 years, time series data used in this research that are consisted coninvestment, employment. Another data are number of economic data representing the industrial area variables, such as PDRB data of Klaten, Purworejo, Wonogiri, and Magelang Regency which represents spillover regional. The model is estimated using OLS (ordinary least squares). The results of the analysis of regional economic variables shows that the labor quantity is a significantly positive to PDRB of Yogyakarta, while investment and the number of industrial- are not significantly affect PDRB, the investment variable in PMA and PMDN data, turn out these investment flows occur in many activities that do not impact on the PDRB. While from the spillover of regional variables, it shows that only regencies that have similar economic characteristics that significantly influence the PDRB of Yogyakarta.